Evaluating Profitability and Efficiency of the Banks in Palestine - Zimmo, Basel (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Nowadays, the role of banks in economics is undeniable. All the financial activities are depending on them because they help to develop the economy quickly, so the profitability measurements of the banking system should be investigated. The goal of this study is to find the profitability measurements for 7 commercial Palestinian banks and the researcher will do that on an analysis of bank for the period 2007-2013. The Palestinian banks profitability will be done by evaluating two main parts of ratios; the first one is the bank specific ratios which are capital adequacy ratio, liquidity ratio, management efficiency ratio, and the last one is the asset quality ratio. In addition, the second part is macroeconomic determinants (inflation and interest rate). In this research, panel data is used to evaluate the relationship between the variables. The study followed the previous studies such as the case of Turkey (Alper and Anbar, 2011) that investigated the profitability to measure the bank-specific performance for 10 commercial banks for the period of 2002-2010 and they came out that there is a positive relationship between the interest rate and profitability and this result agrees with the statistical analysis for of this study’s case.The study concluded that the macroeconomic factors have more impact to the profitability of the banks in Palestine when compared to the bank specific determinants that exist because of the special structure of each bank, so for that the researcher concluded the study by suggesting some solutions to the problems faced in this study.

ÖZ: Günümüzde bankaların ekonomideki rolü inkar edilemez.Onlar finansal faaliyetlerin kalbidir ve ekonomik kalkı nma hızını artırmak için yardımcı olurlar. böylece bankacılık sisteminin karlılığı belirleyicileri değerlendirilmelidir. Bu tezin amac 7 ticari Filistin bankalarının karlılık belirleyicilerinib bulmak için 2007-2013 dönemi için bir banka analizi yapmaktır. Filistin bankalar karlılık makroekonomik belirleyicileri olarak sermaye oranı aktif kalitesi oranı yönetim verimliliği oranı banka-özel ve enflasyon ve faiz oranı gibi likidite oranını uygulayarak tarafından incelenir. Bu araştırmada panel değerlendirilme tarihi ilişkisi kullanılmıştır.Çalışma sonucu değerlerinin makroekonomik belirleyicileri tarafından belirlendigi ve karlılık oranın filistin bankalarında farklı oldugu anlaşıldı çünk her bankanın özel bir kar oran belirleyicisi vardır ve Filistin bankalarının makroekonomik etkilerinden farklı oldugu anlaşılıyor.Biz bu çalışmada karşılaşılan sorunlara bazı çözümler önerdik.
Master of Science in Banking and Finance. Thesis (M.S.).Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2015. Supervisor: Assoc. Prof. Dr. Nesrin Özataç.
Keywords: Banking and Finance; Banking and Finance - Palestine; Palestine; panel data; bank profitability; macroeconomics factor; bank specific determinants